The Political Response of Millennial Generation to the Replacement of the Prosperous Justice Party (PKS) Logo - Irwani, Anton; Mikail, Kiki; Adytyas, Nico Oktario (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The objective of this study is to understand the political response of millennials to the logo change of the Prosperous Justice Party (PKS), focusing on a case study involving students from the Islamic Politics Department at the Faculty of Adab and Humanities. The results of this study indicate that the changes made by PKS have impacted millennials, who perceive PKS as fresher, more youthful, and optimistic. With the logo change, PKS has successfully conveyed the party's vision and mission and its efforts to engage more closely with the millennial generation. This is attributed to the party's symbol, including its color, typography, and imagery, which are memorable, unique, and easily understood. The change not only brings a positive image to the party but also increases millennials' interest in getting to know PKS by seeking further information about the party, thereby enhancing their political awareness and understanding of PKS. However, this effect has yet to be proven during the 2024 election contest. It remains to be seen how voters will respond to PKS in the 2024 elections.